Trinity Strikes Back : Monetary Independence and Inflation in the Caribbean - Cevik, Serhan (IMF Working Papers; Working Paper ;, 2019)
Monetary independence is at the core of the macroeconomic policy trilemma stating that an independent monetary policy, a fixed exchange rate and free movement of capital cannot exist at the same time. This study examines the relationship between monetary autonomy and inflation dynamics in a panel of Caribbean countries over the period 1980-2017. The empirical results show that monetary independence is a significant factor in determining inflation, even after controlling for macroeconomic developments. In other words, greater monetary policy independence, measured as a country's ability to conduct its own monetary policy for domestic purposes independent of external monetary influences, leads to lower consumer price inflation. This relationship-robust to alternative specifications and estimation methodologies-has clear policy implications, especially for countries that maintain pegged exchange rates relative to the U.S. dollar with a critical bearing on monetary autonomy.